Composite indicators in experimental psychology. An example with the semantic space of taste and shape stimuli stimuli. Issue 1 (2nd January 2022) - Marozzi, Marco; Marmolejo-Ramos, Fernando
Abstract: While composite indicators have been used in psychological sciences, they have mostly been confined within the area of social psychology for the assessment of specific issues in quality of life and health. In the area of experimental psychology composite indicators are far less familiar. This paper has the goal of presenting a procedure to design composite indicators that can be used for the analysis of experimental stimuli. An assessment of the extent to which matched taste and shape stimuli share a common semantic space shows the practical usefulness of the procedure. The robustness of the results was studied using uncertainty analysis.